Missing the target: including perspectives of women with overweight and obesity to inform stigma‐reduction strategies. (8th February 2017) - Puhl, R. M.; Himmelstein, M. S.; Gorin, A. A.; Suh, Y. J.
Summary: Objective: Pervasive weight stigma and discrimination have led to ongoing calls for efforts to reduce this bias. Despite increasing research on stigma‐reduction strategies, perspectives of individuals who have experienced weight stigma have rarely been included to inform this research. The present study conducted a systematic examination of women with high body weight to assess their perspectives about a broad range of strategies to reduce weight‐based stigma. Methods: Women with overweight or obesity ( N  = 461) completed an online survey in which they evaluated the importance, feasibility and potential impact of 35 stigma‐reduction strategies in diverse settings. Participants (91.5% who reported experiencing weight stigma) also completed self‐report measures assessing experienced and internalized weight stigma. Results: Most participants assigned high importance to all stigma‐reduction strategies, with school‐based and healthcare approaches accruing the highest ratings. Adding weight stigma to existing anti‐harassment workplace training was rated as the most impactful and feasible strategy. The family environment was viewed as an important intervention target, regardless of participants' experienced or internalized stigma. Conclusion: These findings underscore the importance of including people with stigmatized identities in stigma‐reduction research; their insights provide a necessary and valuable contribution that can inform ways to reduce weight‐based inequities and prioritize such efforts.